Model of achievement goal influencing academic achievement: moderated by perceived teacher instructional practices / Amirah Mohd Juned - Mohd Juned, Amirah (2022)
Among the many factors contributing to the students' competency in learning are students' goal and teacher instructional practices. Goal is concerned of the end result that is centered on competence. Four dimensions of achievement goal were being investigated; performance approach, mastery approach, mastery avoidance and performance avoidance. On the other hand, four constructs of perceived teacher instructional practices were identified which were mastery oriented, performance oriented, differentiated instruction, and cognitive stimulation and autonomy. The sample comprised of 400 secondary school students from ordinary high school in Selangor state and responded to a set of questionnaires after their final year examination. The regression analysis shows that performance avoidance only predicted achievement in English subject. Meanwhile, mastery avoidance predicted students' academic achievement for all three subjects. To test moderator variable which was perceived teacher instructional practices, hierarchical regression was used. Based on the hierarchical regression, mastery approach was directly predicted students' achievement for English subject through the moderation of perceived teacher instructional practices. Meanwhile, cognitive stimulation and autonomy moderated the relationship between mastery avoidance and academic achievement for Mathematics and Science subjects. Besides that, differentiated instruction only moderated the relationship achievement goal with academic achievement for Science subject. It can be concluded that the relationship between mastery avoidance and performance avoidance with academic achievement could be moderated by perceived teacher instructional practice (differentiated instruction, and cognitive stimulation and autonomy). This indicated that teacher instructional practices that were perceived by students have influenced on students' purpose in learning and directly affect their academic achievement.